High protein prescription in methylmalonic and propionic acidemia patients and its negative association with long-term outcome. Issue 5 (May 2021) - Molema, F.; Haijes, H.A.; Janssen, M.C.; Bosch, A.M.; van Spronsen, F.J.; Mulder, M.F.; Verhoeven-Duif, N.M.; Jans, J.J.M.; van der Ploeg, A.T.; Wagenmakers, M.A.; Rubio-Gozalbo, M.E.; Brouwers, M.C.G.J.; et al.
Summary: Background and objective: Methylmalonic acidemia (MMA) and propionic acidemia (PA) are inborn errors of metabolism. While survival of MMA and PA patients has improved in recent decades, long-term outcome is still unsatisfactory. A protein restricted diet is the mainstay for treatment. Additional amino acid mixtures (AAM) can be prescribed if natural protein is insufficient. It is unknown if dietary treatment can have an impact on outcome. Design: We performed a nationwide retrospective cohort study and evaluated both longitudinal dietary treatment and clinical course of Dutch MMA and PA patients. Protein prescription was compared to the recommended daily allowances (RDA); the safe level of protein intake as provided by the World Health Organization. The association of longitudinal dietary treatment with long-term outcome was evaluated. Results: The cohort included 76 patients with a median retrospective follow-up period of 15 years (min–max: 0–48 years) and a total of 1063 patient years on a protein restricted diet. Natural protein prescription exceeded the RDA in 37% (470/1287) of all prescriptions and due to AAM prescription, the total protein prescription exceeded RDA in 84% (1070/1277). Higher protein prescriptions were associated with adverse outcomes in severely affected patients. In PA early onset patients a higher natural protein prescription was associated with more frequent AMD. In MMA vitamin B12 unresponsive patients, both a higher total protein prescription and AAM protein prescription were associated with more mitochondrial complications. A higher AAM protein prescription was associated with an increased frequency of cognitive impairment in the entire. Conclusion: Protein intake in excess of recommendations is frequent and is associated with poor outcome.